Comparative Analysis of Dopaminergic and Cholinergic Mechanisms of Sensory and Sensorimotor Gating in Healthy Individuals and in Patients With Schizophrenia - Proshin, Andrey T. (Frontiers in Behavioral Neuroscience, 2022)
Sensory and sensorimotor gating provide the early processing of information under conditions of rapid presentation of multiple stimuli. Gating deficiency is observed in various psychopathologies, in particular, in schizophrenia. However, there is also a significant proportion of people in the general population with low filtration rates who do not show any noticeable cognitive decline. The review article presents a comparative analysis of existing data on the peculiarities of cholinergic and dopaminergic mechanisms associated with lowering gating in healthy individuals and in patients with schizophrenia. The differences in gating mechanisms in cohorts of healthy individuals and those with schizophrenia are discussed.